2016
DOI: 10.1016/j.ijdevneu.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition is cytotoxic to oligodendrocyte precursor cells in vitro and in vivo

Abstract: Histone deacetylase (HDAC) inhibition mediated by small molecule HDAC inhibitors (HDACi) has demonstrated divergent effects including toxicity towards transformed cell lines, neuroprotection in neurological disease models, and inhibition of oligodendrocyte precursor cell (OPC) differentiation to mature oligodendrocytes (OL). However, it remains unknown if transient HDAC inhibition may promote OPC survival. Using mouse cortical OPC primary cultures, we investigated the effects of the FDA approved pan-HDACi sube… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 72 publications
(101 reference statements)
1
13
0
Order By: Relevance
“…Interestingly, although strongly influenced by the environmental clues, oligodendrocytes are able to complete their differentiation process both in vitro and in vivo in the absence of neurons to be myelinated [ 40 , 41 ]. This ability of oligodendrocytes to terminally maturate even when maintained as monocultures, enables their use as in vitro models for various applications, like, for instance, testing drugs and neurotoxicants, or disease modelling [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, although strongly influenced by the environmental clues, oligodendrocytes are able to complete their differentiation process both in vitro and in vivo in the absence of neurons to be myelinated [ 40 , 41 ]. This ability of oligodendrocytes to terminally maturate even when maintained as monocultures, enables their use as in vitro models for various applications, like, for instance, testing drugs and neurotoxicants, or disease modelling [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the application of sodium butyrate (SB, another histone deacetylase inhibitor) was reported to protect against hypoxia-ischemia-induced loss of neuroblasts and OPCs (Ziemka-Nalecz et al, 2017). On the contrary, SAHA (suberoylanilide hydroxamic acid, a pan-HDACi) negatively impacts OPC survival and may be detrimental to the myelinating brain and spinal cord (Dincman et al, 2016), challenging its potential applications in the treatment of psychiatric and neurodegenerative conditions (Baltan, Murphy, Danilov, Bachleda, & Morrison, 2011;Liu et al, 2012;Lv, Han, Sun, Wang, & Dong, 2012;Lv et al, 2011).…”
Section: Targeting Hdacs In Cns Demyelination Diseasesmentioning
confidence: 99%
“… 30 31 However, many studies demonstrate that nitrous oxide at 75 vol% and xenon at 50 vol% can reduce cortical brain damages in vivo , and decrease NMDA-evoked Ca 2+ influxes of neuronal cell, which is a process which is considered as a major primary event involved in the excitotoxic neuronal death. 32 The neuroprotective action of nitrous oxide at 75 vol% and of xenon at 50 vol% after middle cerebral artery occlusion (MCAO) in vivo may account for their pharmacologically antagonistic properties at the NMDA receptor, 33 because the gas have no effect to the α-amino-3-hydroxy-5-methyl-4-isoxazoleproprionic acid receptor. 17 So many dates of studies have shown that nitrous oxide and xenon keep normal cells from excitotoxic neuronal death produced by stimulating either glutamate or NMDA in cortical cell cultures.…”
Section: E Xperimental S Tudies Of mentioning
confidence: 99%